A new species of Talitridae (Amphipoda: Gammaridea) from Tioman Island, Malaysia - Othman, B. H.r.; Azman, B. A.r. (Zootaxa, 2007)
The amphipod crustacean Talorchestia morinoi sp. nov. collected on the west coast of Tioman Island, Malaysia is described and illustrated.  So far no species belonging to the genus is known from Malaysia and this is the first record of the family Talitridae from Malaysia.  Differences between the new species and related species within the Talorchestia sensu Morino & Miyamoto, 1988 group are discussed and a key is also included.